Um filtro gaussiano adaptativo para análise comparativa de imagens de radares e satélites meteorológicos - Garcia, João Victor Cal; Stephany, Stephan; Calheiros, Roberto Vicente [UNESP]; d'Oliveira, Augusto Brandão [UNESP] (My University, 2011)
Meteorological satellite and radar data comparative analysis allows to correlate the precipitation structures observed in both images. Such analysis would make feasible the extension of the range of ground-based meteorological radars. In addition to the different spatial and temporal resolution of these images this comparative analysis presents difficulties due to the effects of rotation and distortion, besides the different formats, projections, and coordinate systems. This work employed an approach based on a Gaussian adaptive filter in order to compare such images. The statistical results obtained from the comparison of the images are matched to those produced by other methods.

A aplicação do radar meteorológico em irrigação vem tendo crescente desenvolvimento. O uso sinérgico de informações de outros sensores destacando-se ai as de satélites meteorológicos, agrega valor significativo em muitos casos. A análise conjunta de imagens de satélites e radares meteorológicos permite correlacionar estruturas precipitantes observadas em ambas as imagens. Essa análise tornaria viável a extensão do alcance de radares em meteorológicos em terra. Entretanto, além das resoluções espaciais e temporais diferentes dessas imagens, análise comparativa é dificultada devido a efeitos de rotação, distorção geométrica e aos diferentes formatos de dados, projeções geográficas e sistemas de coordenadas. Neste trabalho, emprega-se uma abordagem baseada num filtro gaussiano adaptativo para comparação dessas imagens. Os resultados estatísticos obtidos da comparação são confrontados com aqueles obtidos por outros métodos existentes.
An adaptive Gaussian filter for the comparative analysis of images from meteorological radar and satellites
Keywords: Image filtering; Irrigation; Meteorological radar; Meteorological satellite; comparative study; Gaussian method; image analysis; image resolution; irrigation; meteorology; radar; satellite; spatial resolution